INTEGRATION OF THEORY AND PRACTICE IN SOCIAL WORK: CHALLENGES AND TRIUMPHS - Carelse, Shernaaz; Dykes, Glynnis (Social Work/Maatskaplike Werk, 2014)
Teaching (in any discipline) is rewarding when students show the required growth and development in terms of their knowledge, skills and attitude (within the social work context) (Kadushin & Harkness, 2002). So it is disappointing when, in completing various assessment tasks, some students do not achieve the learning objectives set for a given task. The most troubling within the UWC context was the challenges students experienced on the third year level in integrating their theoretical knowledge with their practice learning.